The Art of Tacit Learning in Serious Location-Based Games - Sheahan, Jacob; Davies, Hugh; Hjorth, Larissa (Frontiers in Education, 2021)
Over the past two decades, location-based games have moved from media art fringes to the mass cultural mainstream. Through their locative affordances, these game types enable practices of wayfaring and placemaking, with the capacity to deliver powerful tacit knowledge. These affordances suggest the potential for the development of location-based games in educational contexts. This paper presents three cases studies—TIMeR and Wayfinder Live and Pet Playing for Placemaking—to illustrate how each uses elements of wayfaring and placemaking to bring new opportunities for education through a tacit knowledge approach.